Environmental Sustainability Practices in Large Brazilian Food Companies in Light of the 2030 Agenda Goals (Global Journal of Human-Social Science, 2024)
The study aims to identify and discuss practices aimed at environmental sustainability in large Brazilian food companies in light of the 2030 Agenda goals and of the commitments made by the Brazilian Food Industry Association (ABIA) at Rio+20. The survey is of an applied, qualitative, exploratory nature and descriptive design, with documentary data collection anchored in the sustainability reports of sizeable Brazilian food companies selected for the study. Unlike the studies carried out in Brazil and other parts of the world, in this study, management for environmental sustainability was assessed in the light of the goals and targets set out in the 2030 Agenda. The results indicate that there has been progress in the Brazilian Food Industry about the commitments made in favor of sustainable development. Many measures adopted satisfactorily meet the objectives of the 20230 Agenda. However, intensifying of these practices is still necessary so that the industry effectively contributes to achieving a legitimate and acceptable level of sustainable development, especially in a country like Brazil, where the food and agriculture industry compete for space with biomes and sensitive ecosystems the activity economic.